Consciousness as the collective excitation of a brainwide web – understanding consciousness from below quantum fields to above neuronal networks. (September 2019) - Lidström, Suzy; Allen, Roland E
Abstract: In the spirit of previous ideas in the neuroscience community, but with a more physics-oriented perspective, we propose that consciousness can be described as the collective excitation of a brainwide web of neurones. This picture is inspired by the fact that, in all major areas of physics, a collective excitation has just as much physical reality as a particle or other localized object. The brainwide web extends into those regions (neuronal networks) where processed information is received from the senses, memories, etc. (emerging out of unconscious processes in prior networks). It unifies those regions (plus motor control regions) via the vast complexity of the neuronal interactions that it spans. A crude analogy is the worldwide web, which extends into servers which have been prepared by external agents. Other crude analogies are the many collective excitations in physics. True understanding of consciousness must rely mostly on experiment, but since probes of living brains have limited precision, there is an important role for large-scale simulations in revealing details and complementing experiment. Petascale computational facilities should make it possible to perform simulations with realistic complexity.